Bridging Formal Legality and Living Law Public Prosecutorial Policies to Achieve Justice - Anis Mashdurohatun; Mahmoud W M Abu Wazna; Mahmoud Elsayed Atyea Abdasmad; Joman Rabah Mahfouth Alkhatib (Contrarius, 2026)
Recognition of living law: Article 2 of Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift in Indonesian criminal law from the principle of formal legality to material legality. However, this change has not been accompanied by an update to criminal procedural law. In fact, Criminal Procedure Code (KUHAP) remains oriented towards legal positivism and does not provide a procedural mechanism to integrate existing social norms into criminal justice practices. This situation creates tension between legal pluralism, legal certainty, and demands for substantive justice in the criminal justice system. This study aims to analyse: (1) the position of the Criminal Procedure Code in accommodating living law in the criminal justice process; (2) the role of the Prosecutor's Office as dominus litis in integrating living law through prosecution policy; and (3) the reconstruction model of prosecution policy in the perspective of ius constituendum in order to realize the integration between formal legality and material legality. The study uses a normative legal research method with a statutory, conceptual, and comparative approach, and is analysed using the theory of justice, the Pancasila theory of justice, and Gustav Radbruch’s theory of legal values. The results of the study indicate that: (1) the Criminal Procedure Code functions as a procedural law based on formal legality so that it has not been able to operationalize the recognition of living law procedurally; (2) the Prosecutor's Office has in fact accommodated living law through prosecutorial discretion and restorative justice, but does not yet have systemic procedural legitimacy; and (3) reconstruction of prosecution policy is needed through a facilitation model by prosecutors, judicial verification, court decisions, and state execution in order to balance legal certainty, substantive justice, and social benefits in the Indonesian criminal justice system.